Hernia Surgery - Sözen, Selim; Erdem, Hasan (IntechOpen, 2022)
A hernia occurs when an internal organ pushes through a weak spot in the body's muscle or tissue. There are several types of hernia, including inguinal hernias, femoral hernias, umbilical hernias, and hiatal hernias. Hernias usually do not get better on their own and surgery may be the only way to repair them. This book discusses different types of hernias and hernia surgeries, including open surgery, laparoscopic surgery, and robotic repair.